Planting The Aswaja Concept in Islamic Boarding Schools in Jambi City; Deradicalization Strategy - Hadri Hasan; A A Musyaffa (World Journal of Islamic Learning and Teaching, 2024)
This research reviews the concept and role of Aswaja lessons at Islamic boarding schools, especially at Islamic boarding schools in Jambi City, in de-radicalization efforts. As is known, radicalization increasingly developed after the fall of the New Order. The Reformation era opened up various forms of expression, including religious expression. The increasing development of radicalization has given rise to widespread public unrest. Various responses emerged, including through counter-ideology. Aswaja is believed to be able to prevent the growth of radicalization. The data presented in this article comes from observations, interviews at Islamic boarding schools in Jambi City; As'ad Islamic boarding school in Jambi City, Saadatul Daren Jambi City and Al Hidayah Islamic boarding school in Jambi City as well as literature review related to the topic of writing. The argument built in this paper is that the reconstruction and actualization of the values contained in Aswaja can be firmly internalized within a santri. The strategies and policies carried out by Islamic boarding schools are important in the socialization and internalization of Aswaja. applying Aswaja subjects and materials, as well as a moderate level of religious understanding among the students Based on test results, the level of moderate understanding among students is as follows: National commitment is 86, maintaining religious tolerance in society is 88, anti-violence is 87 and views and respect for local traditions and culture is 87. Thus, there is a change in religious moderation views in the students after learning the concept of aswaja